Assessing the Impact of the October 2020 Capena Earthquake on the Lago Puzzo Sinkhole (San Martino Valley, Rome, Italy): Seismological, InSAR, and Geophysical Evidence of Possible Causal Relationships - R. De Ritis; G. Rotella; C. Tolomei; G. Calderoni; F. Marra; A. Argentieri; P. Vitali; M. Fabiani; M. Chiappini; C. Doglioni (Pure and Applied Geophysics, 2025)
In October 2020, a low-magnitude earthquake struck near the village of Capena, approximately 30 kilometers north of Rome. This seismic event was particularly remarkable due to its shallow hypocenter and the complete absence of aftershocks. Additionally, both during and after the event, residents reported hearing loud rumbling noises on multiple occasions in the village and surrounding rural areas. The earthquake's epicenter is located in a sinkhole-prone region intersected by major infrastructure, including a high-speed railway, high-voltage power lines, and a provincial road. Given these conditions, public authorities and regional Civil Protection agency closely monitored the area, prompting a comprehensive investigation. The study adopted an interdisciplinary approach to assess the stability of sinkhole-prone zones and identify any geological changes potentially triggered by the earthquake. A key focus of the research was the "Lago Puzzo," a well-documented example of multiphase, still active, sinkhole evolution within the San Martino Valley, alongside other similar extinct features in the area. The investigation integrated three primary methodologies: spectral analysis of seismic data to characterize the October 2020 event; remote sensing (SAR) using InSAR analysis to map ground displacement; geophysical surveys (ERT) to reveal subsurface structures. Although the study found no direct correlation between the earthquake and the evolution of Lago Puzzo, the results provide valuable insights into the current deformation state of the sinkhole and offer projections for its potential future development. Ultimately, this research represents a significant step forward in refining hazard assessment methods for the region.

Haptic and visuo-haptic impairments for object recognition in children with autism spectrum disorder: focus on the sensory and multisensory processing dysfunctions - G. Purpura; S. Petri; R. Tancredi; F. Tinelli; S. Calderoni (Experimental Brain Research, 2024)
Dysfunctions in sensory processing are widely described in individuals with autism spectrum disorder (ASD), although little is known about the developmental course and the impact of these difficulties on the learning processes during the preschool and school ages of ASD children. Specifically, as regards the interplay between visual and haptic information in ASD during developmental age, knowledge is very scarce and controversial. In this study, we investigated unimodal (visual and haptic) and cross-modal (visuo-haptic) processing skills aimed at object recognition through a behavioural paradigm already used in children with typical development (TD), with cerebral palsy and with peripheral visual impairments. Thirty-five children with ASD (age range: 5–11 years) and thirty-five age-matched and gender-matched typically developing peers were recruited. The procedure required participants to perform an object-recognition task relying on only the visual modality (black-and-white photographs), only the haptic modality (manipulation of real objects) and visuo-haptic transfer of these two types of information. Results are consistent with the idea that visuo-haptic transfer may be significantly worse in ASD children than in TD peers, leading to significant impairment in multisensory interactions for object recognition facilitation. Furthermore, ASD children tended to show a specific deficit in haptic information processing, while a similar trend of maturation of visual modality between the two groups is reported. This study adds to the current literature by suggesting that ASD differences in multisensory processes also regard visuo-haptic abilities necessary to identify and recognise objects of daily life.

Effect of the axial force on shear and flexural strength of masonry spandrels - A. Sandoli; B. Calderoni; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Correction to: “Predictive hybrid fragility models for urban scale seismic assessment: a case study in Basilicata Region (Italy) - A. Sandoli; G. Pacella; B. Calderoni; G. Brandonisio; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Predictive hybrid fragility models for urban scale seismic assessment: a case study in Basilicata Region (Italy) - A. Sandoli; G. Pacella; B. Calderoni; G. Brandonisio; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Seismic vulnerability assessment of minor Italian urban centres: development of urban fragility curves - A. Sandoli; B. Calderoni; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2022)
This paper presents a novel hybrid-based methodology devoted to develop urban fragility curves and damage probability matrices to predict likelihood seismic damage scenarios for small and medium Italian urban centres, considering URM buildings only. The concept of urban fragility curve consists of a single curve mean-representative of the seismic fragility of an entire area accounting for the combinations of building classes and their percentage, then they differ from those typological. The methodology has been developed with reference to Rocca di Mezzo, a small Italian urban centre located in the central Apennine area, Italy. Based on CarTiS inventory, building classes have been firstly recognized and urban fragility curves, representative for damage scenarios at Ultimate Limit State, developed. To predict damage scenarios from low to high-intensity earthquakes, an approach to define multi-damage urban fragility curves and damage probability matrices has been also presented. To this aim, a damage scale suffered by building classes has been defined by converting the final outcomes of the AeDES form (used in Italy for post-earthquake surveys) in the damage levels provided by the European Macroseismic Scale (EMS98). Data coming from urban fragility curves have been compared with the actual damage scenario recorded in Rocca di Mezzo after the 2009 L’Aquila’s earthquake, in terms of both peak-ground acceleration and Mecalli-Cancani-Sieberg scale. The achieved results showed a good accordance between theoretical predictions and actual damage scenarios, coherent also with the damage scenarios occurred in other Italian historical centres hit by severe earthquakes over the years. Thus, the methodology can provide a first important indicator to support the development of emergently plans devoted to identify priority of interventions in such areas particularly vulnerable with respect to others.

Fragility curves for Italian URM buildings based on a hybrid method - A. Sandoli; G. P. Lignola; B. Calderoni; A. Prota (Bulletin of Earthquake Engineering, 2021)
A hybrid seismic fragility model for territorial-scale seismic vulnerability assessment of masonry buildings is developed and presented in this paper. The method combines expert-judgment and mechanical approaches to derive typological fragility curves for Italian residential masonry building stock. The first classifies Italian masonry buildings in five different typological classes as function of age of construction, structural typology, and seismic behaviour and damaging of buildings observed following the most severe earthquakes occurred in Italy. The second, based on numerical analyses results conducted on building prototypes, provides all the parameters necessary for developing fragility functions. Peak-Ground Acceleration ( PGA ) at Ultimate Limit State attainable by each building’s class has been chosen as an Intensity Measure to represent fragility curves: three types of curve have been developed, each referred to mean, maximum and minimum value of PGA s defined for each building class. To represent the expected damage scenario for increasing earthquake intensities, a correlation between PGA s and Mercalli-Cancani-Sieber macroseismic intensity scale has been used and the corresponding fragility curves developed. Results show that the proposed building’s classes are representative of the Italian masonry building stock and that fragility curves are effective for predicting both seismic vulnerability and expected damage scenarios for seismic-prone areas. Finally, the fragility curves have been compared with empirical curves obtained through a macroseismic approach on Italian masonry buildings available in literature, underlining the differences between the methods.